Identification of Human Resource Management Best Practices in the MSME Sector - Abd. Karman; Purnomo; Akbar Jaya; Teguh Setiawan Wibowo (Enrichment : Journal of Management, 2022)
This study aims to obtain evidence of scientific support from existing publications so that we can answer the problem of this study, namely identifying superior and destructive human resource management in the MSME sector. Then we make the data online from many sources that we believe can answer the problem. We have collected 60 relevant publications from the data and discussion to answer this study, limiting the barrier from 2010 to 2022. Our study was carried out under a phenomenological approach where we wanted to get answers from several existing data so that our findings could get answers. Based on the study and the results of the discussion, we can summarize that some best practices have contributed to the success of MSMEs, including having superior human resources and having the best, which includes understanding how to sell MSME products, having the soul to serve consumers with care and understanding decision-making solutions then placing the customer's face, and having financial and generational governance capabilities following the needs of MSMEs in the era of free competition.